THE TASK FORCE FOR THE MANAGEMENT OF VALVULAR HEART DISEASE OF THE EUROPEAN SOCIETY OF CARDIOLOGY (ESC) AND THE EUROPEAN ASSOCIATION FOR CARDIO-THORACIC SURGERY (EACTS) 2017 ESC/EACTS GUIDELINES FOR THE MANAGEMENT OF VALVULAR HEART DISEASE (TEXT IS AVAILABLE IN ELECTRONIC VERSION) - Article Editorial (Российский кардиологический журнал)
.